R
2
=
9.61
O
h
m
s
Step-by-step explanation:
l
1
=
18
m
r
1
=
1.2
2
=
0.6
m
m
=
6
⋅
10
−
4
m
R
1
=
10
O
h
m
s
R
1
=
τ
⋅
l
π
⋅
r
2
1
R
1
=
τ
⋅
18
π
⋅
36
⋅
10
−
8
10
=
τ
⋅
18
36
⋅
π
⋅
10
−
8
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
l
2
=
27
m
r
2
=
1
⋅
5
2
=
0.75
⋅
10
−
3
=
7.5
⋅
10
−
4
m
R
2
=
τ
⋅
l
2
π
⋅
r
2
2
R
2
=
τ
⋅
27
π
⋅
56.2
⋅
10
−
8
R
2
=
τ
⋅
27
56.2
π
⋅
10
−
8
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
...
.
.
10
R
2
=
τ
⋅
18
36
⋅
π
⋅
10
−
8
⋅
56.2
⋅
π
⋅
10
−
8
τ
⋅
27
10
R
2
=
18
⋅
56.2
36
⋅
27
10
R
2
=
56.2
54
R
2
=
540
56.2
R
2
=
9.61
O
h
m
s